The game changer: Regulatory reform and multiple credit ratings - Huang, He; Svec, Jiri; Wu, Eliza (Journal of Banking & Finance, 2021)
This paper examines the change in the regulatory use of multiple credit ratings after the Dodd-Frank Act (Dodd-Frank). We find that post Dodd-Frank reform, firms are less likely to demand a third rating (typically from Fitch) for ratings near the high yield (HY) - investment grade (IG) boundary to support their new corporate bond issues. Third ratings also become less informative post Dodd-Frank, with a much weaker market impact on credit spreads for firms with S&P and Moody's ratings on opposite sides of the HY-IG rating boundary. We provide new evidence on the effect of Dodd-Frank in curbing corporate borrowers’ strategic use of multiple credit ratings near this boundary.